Exploring Cooperative Domain Dynamics in Thermus thermophilus Leucyl-tRNA Synthetase Using Low-Frequency Normal Mode Calculations and Statistical Coupling Analysis. - Weimer, Kristina; Shane, Brianne; Brunetto, Michael (My University, 2009)
Leucyl-tRNA synthetases are class I synthetases that catalyze the covalent attachment of leucine to the tRNAL. The three-dimensional crystal structure of Thermus thermophilus leucyl-tRNA synthetase (TtLeuRS) demonstrates a complex modular architecture where three flexible domains [the conserved connective polypeptide 1 (CP1) domain (residues 224-417), the leucine-specific (LS) domain (residues 577-634), and the zinc-1 (ZN-1) binding domain (residues 154-189)] are inserted into the central catalytic domain. In the present work, we have investigated the collective motion of various structural elements in TtLeuRS using normal mode calculations.
Color poster with text and disgrams describing research conducted by Kristina Weimer, Brianne Shane, and Michael Brunetto, advised by Sudeep Bhattacharyay and Sanchita Hati.
Keywords: RNA; Aminoacyl-tRNA synthetase; Leucine; Amino acids; Posters